Economic Load Dispatch Model Optimization using Fuzzy Interactive Optimization Technique - Dey, Samir; Ray, Abhinab; Goswami, Subhadip; Roy, Kousik (International Journal of Computer Sciences and Engineering, 2025)
Environmental awareness and the recent environment protecting policies have extremely spurred many electric utilities to regulate their practices to account for the emission impacts. This paper proposes a new fuzzy multi-objective optimization approach to solve a multi-objective nonlinear programming problem in context of a power system optimization model. We have been developed a multi-objective power system optimization model in fuzzy environment. Here, the objectives are (i) to minimize the fuel cost and (ii) to minimize the emission level simultaneously while satisfying the power balance and generation limit constraints. In this model, the design variables are the generator power output. The model is tackled through interactive fuzzy optimization technique and the approach is tested on a system of 3-generators with transmission losses. The empirical results demonstrate the effectiveness of the proposed method.